Effect of High-Fat Diet on Spatial Learning and Memory and Regulatory Role of N-Methyl-D-Aspartate Receptors in the Dentate Gyrus - LIU Huaying, DONG Wei, ZHANG Zihan, LI Yingshun, JIN Qinghua (Shipin Kexue)
Newly weaned rats were fed with high-fat diet (HFD) (containing 45% fat) for 12 weeks, and body mass, serum lipid and glucose levels were observed. The Morris water maze (MWM) test was used to evaluate the spatial learning and memory capacity of the rats; Western blot was used to detect the expression of phosphorylated Ca2+/calmodulin dependent protein kinase II (p-CaMKII) and cAMP-response element binding protein (p-CREB), pro-inflammatory cytokines, including interleukin-6 (IL-6) and IL-1β in the hippocampal dentate gyrus (DG); the expression of ionized calcium binding adapter molecule 1 (Iba1) in the DG were observed by Western blot and immunohistochemistry. Furthermore, the role of N-methyl-D-aspartate (NMDA) receptors in the above changes was examined by microinjection of the NMDA receptor blocker MK-801 into the DG. Our results showed that the rats developed diet-induced obesity (DIO) after long-term HFD consumption compared with the control (CON) group. Body mass and the levels of serum triglyceride, total cholesterol, and low-density lipoprotein were significantly increased in the DIO and DIO + MK-801 injection groups. In the MWM test, compared with the CON group, spatial learning and memory capacity was impaired in the DIO group, and microinjection of MK-801 into the DG rescued these impairments. Compared with the CON group, the expression of p-CaMKII and p-CREB was significantly decreased and the expression of Iba1, IL-6 and IL-1β in the DG was significantly increased in the DIO group; however, these changes were reversed by microinjection of MK-801 into the DG of DIO rats. Our results suggest that long-term HFD consumption induces DIO and neuroinflammatory responses, and impairs spatial learning and memory. Moreover, blocking of NMDA receptors in the DG rescues spatial learning and memory impairments in DIO rats by activating the CaMKII-CREB signaling pathway and decreasing neuroinflammatory responses. This study provides a theoretical basis for rational diet and understanding the mechanism of HFD-induced impairments in learning and memory.